Using Value-Based Argumentation for Manipulating Voter Preferences - POYRAZ, EMEL (MARMARA UNIV, FAC COMMUNICATION, 2018)
Manipulating voter preferences in favor of a certain political institution or opinion is performed by a lot of different techniques. However, in the process of voter persuasion, it is also a general necessity that the message produced by the political institution is designed in compliance with certain logical principles. Accordingly; politic argumentation on one hand, meets logical qualifications that a message should have, on the other hand, it offers certain technical structures and wording features. In parallel with that, in this study, the use of value-based argumentation in manipulating voter preferences is examined. Within this framework, Referendum of Presidential Government System conducted in 2017 is selected as the object of research. In the context of value-based argumentation, political argumentation analysis has been carried out on written material that AK Party and CHP produced within referendum campaign. As a result of the research, it is determined that three of totally seven AK Party arguments, two of totally nine CHP arguments produced for referendum topics are in harmony with the value-based argumentation style.
Keywords: Political Argumentation; Value-Based Argumentation; The New Rhetoric; Voter Preferences; Political Persuasion